INCREASING PRIMARY CLASS STUDENTS' INTEREST IN FINE ART THROUGH TEACHING THE CREATIONS OF UZBEKISTAN FOLK ARTISTS - Qambarova Nasibaxon Ma’rufjon qizi (Journals Park Publishing, 2024)
This article provides extensive information about the life and work of the people's artists of Uzbekistan, analyzes their unique works, and provides information about the processes of creating works. At the same time, by teaching the work of artists, it closely helps school-aged and especially elementary school students to increase their interest in visual arts.
Keywords: Uzbekistan, artist, image, creativity, work, color, mood, state, theme, essence, mosaic, stained glass.